Antecedents of Consumer Behavior at Islamic Bank in Indonesia - Miftachul Ulum; Abdul Mun’im (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2021)
The emergence of Islamic banking is based on conventional banking activities that prioritize the interests of gaining profits that are prohibited by Islam and economic aspects which are based on transferring business risks to one party. This study aims to analyze the antecedents of consumer behavior at Islamic Bank in Indonesia. This research is qualitatif, using documentation as method of data collection. Analysis data using qualitatif method. The results found that consumer behavior is influenced by several factors, namely: environmental influences, individual differences and influences, and psychological. However, the process of consumer behavior that is built with the fundamentals of Islamic sharia will provide benefits for a better life in the world and life in the hereafter becomes the ultimate goal of life.